Comparative evaluation of Gingival Crevicular Fluid (GCF) levels of Interleukin-34 levels in periodontally healthy and in patients with chronic and aggressive periodontitis- A cross-sectional study - Parichaya Batra; Sushma Das; Poonam Patel (Elsevier, 2019)
Background and objectives: Proinflammatory cytokines appear to have a central role in the destruction of periodontal tissues. By binding to Receptor Activator of Nuclear Factor κb (RANK) on osteoclast progenitor cells, these cytokines are locally responsible for the activation of bone resorbing osteoclasts differentiation and function. Interleukin-34 (IL-34) is a proinflammatory cytokine derived from the osteoblasts and plays an important role in osteoclastogenesis. The present study was carried out to assess the levels of IL-34 in Gingival Crevicular Fluid (GCF) in periodontally healthy patients, chronic periodontitis and aggressive periodontitis. Materials and method: A total of 90 patients were recruited in the study and were divided into 3 groups: Periodontally healthy patients (Group I), Chronic periodontitis (Group II) and Aggressive periodontitis (Group III). Clinical Parameters like plaque index, gingival index, probing depth, clinical attachment levels were recorded and GCF samples were collected at baseline for the assessment of IL-34 levels in all the three groups. IL-34 levels were calculated using Enzyme-Linked Immune-Sorbent Assay (ELISA). Results: The mean GCF levels of IL-34 in Group I was 47.22 ± 18.04 pg/ml, Group II was 103.76 ± 26.61 pg/ml and in Group III was 191.71 ± 49.24 pg/ml. The mean GCF IL-34 level was found to be higher in Group III followed by Group II and Group I. The IL-34 levels correlated with clinical parameters like plaque index, gingival index, probing depth, clinical attachment levels. But correlation with probing depth and clinical attachment level were significantly higher in Group III followed by Group II and Group I. Interpretation and conclusion: The study demonstrated higher levels of IL-34 in aggressive periodontitis when compared with chronic periodontitis. IL-34, a novel diagnostic marker which was found to be at higher level in GCF of aggressive and chronic periodontitis patients. Keywords: Interleukin-34, Aggressive periodontitis, Chronic periodontitis, Cytokine